2010
DOI: 10.1139/v09-177
|View full text |Cite
|
Sign up to set email alerts
|

Do corresponding coupling constants in hydrogen-bonded homo- and hetero-chiral dimers differ?

Abstract: Ab initio equation-of-motion coupled cluster singles and doubles (EOM-CCSD) calculations have been carried out to evaluate spin-spin coupling constants in six pairs of homo-and hetero-chiral dimers: (HOOH) 2 , (H 2 NNH 2 ) 2 , (FOOH) 2 , (FHNNH 2 ) 2 , (HOOOH) 2 , and (FOOOH) 2 . Corresponding spin-spin coupling constants in these isomeric pairs of C2 and Ci symmetry may differ, but these differences are small and may not be detectable experimentally. For the complexes with O1-HÁÁÁO and O1-HÁÁÁF hydrogen bonds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The stronger binding interaction in the HOOOH cyclic dimer ( 2A , BE = 8.35 kcal/mol, B3LYP) as compared to that in the analogous structure of the HOOH dimer (BE = 7.31 kcal/mol), indicates that hydrogen trioxide is a stronger proton donor (stronger acid) than hydrogen peroxide . A recent theoretical study [MP2/6-311++G(d,p)] indicates that homo- and heterochiral dimers of HOOOH (of C 2 and C i symmetry) differ somewhat in binding energy, but the differences appear to be too small for allowing experimental distinction …”
Section: Structure Acidity/basicity and Thermochemical Data Of Hydrog...mentioning
confidence: 93%
See 1 more Smart Citation
“…The stronger binding interaction in the HOOOH cyclic dimer ( 2A , BE = 8.35 kcal/mol, B3LYP) as compared to that in the analogous structure of the HOOH dimer (BE = 7.31 kcal/mol), indicates that hydrogen trioxide is a stronger proton donor (stronger acid) than hydrogen peroxide . A recent theoretical study [MP2/6-311++G(d,p)] indicates that homo- and heterochiral dimers of HOOOH (of C 2 and C i symmetry) differ somewhat in binding energy, but the differences appear to be too small for allowing experimental distinction …”
Section: Structure Acidity/basicity and Thermochemical Data Of Hydrog...mentioning
confidence: 93%
“…87a A recent theoretical study [MP2/6-311++G(d,p)] indicates that homoand heterochiral dimers of HOOOH (of C 2 and C i symmetry) differ somewhat in binding energy, but the differences appear to be too small for allowing experimental distinction. 96 The binding energies per unit monomer in the trimers are greater than those in the dimers. 87 Thus, there is a slight favorable cooperative effect in forming the long-chain structures.…”
Section: Structure Acidity/basicity Andmentioning
confidence: 99%
“…Hydrogen peroxide and its derivatives have been widely used as models to computationally study chiral properties due to their small size, which makes them very adequate for theoretical studies. Thus, their optical rotatory power (ORP) shows a very interesting dependence on the dihedral angle, providing both positive and negative values in the range 0–180°. , The atomic partition of the ORP has been carried out using the acceleration gauge for the electric dipole and the torque formalisms. , The chiral discrimination of the dimers (homochiral vs heterochiral) has been previously studied for several of its derivatives (HOOX, X = H, CCH, CH 3 , CF 3 , t -C 4 H 9 , CN, F, Cl) , and for large clusters of the parent compound. , The coupling constants of some dimers have been calculated to check the possibility of this property to distinguish between homo- and heterochiral complexes . The inclusion of the solvent effect on the chiral discrimination on the dimers of hydrogen peroxide and its methyl derivatives showed that their relative stability could be reversed due to solvation. , …”
Section: Introductionmentioning
confidence: 99%
“…If this is done, electronic effects, which overrule H‐bonding, can be easily identified as in the case of the mono‐fluorinated hydrazine dimer 4 for which dipole‐dipole attraction becomes decisive. In passing, we note that Del Bene and coworkers recently tried to base chiral discrimination of homo‐ and heterochiral pairs 1–6 on NMR SSCCs. These authors found that the calculated differences in the SSCCs are too small to be detectable experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…A recent example is the chiral recognition of of diastereomeric 6‐cedrols by VCD . Recently, Del Bene and coworkers investigated whether NMR spin‐spin coupling constants (SSCCs) may be a tool for chiral discrimination. They found that, in most cases, the values of the spin‐spin coupling constants differ only marginally so that they cannot be used for chiral discrimination.…”
Section: Introductionmentioning
confidence: 99%